A high thermal conductivity low temperature co-fired ceramic and preparation method thereof

By wrapping BN nanosheets and sintering by sol-gel method, the problem of low thermal conductivity of glass/ceramic-based LTCC materials is solved, and the high thermal conductivity and sintering temperature are improved, and the heat dissipation performance of electronic components is improved.

CN118290032BActive Publication Date: 2024-12-17SHANDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410707351.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2024-12-17
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The thermal conductivity of glass/ceramic-based LTCC materials is low, resulting in insufficient heat dissipation of electronic components, affecting service life and may cause safety hazards, and it is easy to introduce interface thermal resistance when improving thermal conductivity.

Method used

Sintering is carried out by sol-gel method and BN nanosheets are wrapped to build high-thermal conductivity ceramic materials, reduce sintering temperature and improve thermal conductivity, and improve the thermal conductivity of the material by building a core-shell structure.

Benefits of technology

It significantly improves the thermal conductivity of glass/ceramic-based LTCC materials, reduces the sintering temperature, improves the thermal conductivity of the material, and avoids the increase in interface thermal resistance and improves the heat dissipation performance of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118290032B_ABST
    Figure CN118290032B_ABST
Patent Text Reader

Abstract

The present application provides a high thermal conductivity low temperature co-fired ceramic and a preparation method, which relates to the field of electronic information functional materials and integrated circuits. The low temperature co-fired ceramic material comprises a certain content of microcrystalline glass ceramics and 1~5wt% of BN nanosheets. Due to the special properties of BN, BN gradually forms effective, continuous and more thermal conduction paths inside the sample, which promotes phonon transmission and increases thermal conductivity. In addition, by adjusting the mass percentage of BN nanosheets and the glass oxide ratio, the sintering temperature of the low temperature co-fired ceramic material can be below 960°C, and the thermal conductivity is 1.41~1.84W / m·k, which is 106~153% higher than the original thermal conductivity. The new low temperature co-fired ceramic material is expected to improve the current situation where the heat dissipation performance of electronic components such as integrated circuit substrates, radio frequency components and couplers is relatively backward.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic information functional materials and integrated circuits, and in particular to a high thermal conductivity low temperature co-fired ceramic and a preparation method thereof. Background Art

[0002] With the rapid development of the new generation of wireless communication technology, the Internet of Everything, and artificial intelligence systems, the miniaturization and multifunctional integration of electronic components have become the main driving force for the development of microelectronics technology. The integration technology based on low-temperature co-fired ceramic (LTCC) technology has broad development space.

[0003] As electronic modules become more and more integrated and smaller in size, the material selection of module substrates and the heat dissipation of electronic modules become more and more important. If the heat generated by electronic components is not removed in time, it will seriously affect the service life of electronic components, and even worse, it will cause safety accidents. However, microcrystalline glass or glass / ceramic-based LTCC materials have low thermal conductivity, especially glass / ceramic-based LTCC materials have a thermal conductivity of only 0.71~1.34W / m·k. Therefore, it is urgent to improve the thermal conductivity of glass / ceramic-based LTCC materials.

[0004] BN nanosheets exist in hexagonal variants (h-BN) in the variants. The crystal structure is similar to the graphene layered structure and has a large thermal conductivity. Adding BN nanosheets to change the thermal conductivity of the material is to improve the thermal conductivity of the material by constructing an effective thermal conduction pathway, but the interface thermal resistance will be introduced while constructing the thermal conduction pathway. The appearance of a pathway improves thermal conductivity, and the appearance of thermal resistance reduces thermal conductivity, which is in itself a contradictory thing. Therefore, it is very important to find a method that can improve the thermal conductivity of glass / ceramic-based LTCC materials without introducing excessive interface thermal resistance. Therefore, the present invention intends to improve its thermal conductivity by constructing a core-shell structure so that the glass / ceramic-based LTCC material wraps the BN nanosheets. Summary of the invention

[0005] The present application provides a high thermal conductivity low temperature co-fired ceramic and a preparation method thereof, which is synthesized by sol-gel sintering, aiming to improve the thermal conductivity of BN ceramics while having a lower sintering temperature to meet the application of high thermal conductivity low temperature co-fired ceramic technology.

[0006] On the one hand, the present application provides a high thermal conductivity low temperature co-fired ceramic, which is characterized by glass ceramics wrapped with BN nanosheets. The high thermal conductivity ceramic material has a thermal conductivity increased by 106~153% compared to the original one and a sintering temperature reduced by 200~400℃.

[0007] On the other hand, the present application provides a method for preparing a high thermal conductivity low temperature co-fired ceramic, comprising the following steps:

[0008] (1) Ca(NO 3 ) 2 ·4H 2 O, H 3 BO 3 , C 8 H 20 O 4 Si, (CH 3 COO 2 Zn·2H 2 O.NaNO 3 、KNO 3 、Al(NO 3 ) 3 9H 2 O is the precursor, and the mass of the precursor is calculated according to the oxide ratio of the glass ceramic composition and weighed for later use;

[0009] (2) Add the C weighed in step (1) 8 H 20 O 4 Si is fully mixed with ethanol and water, and stirred in a water bath to obtain a mixed solution; after a certain period of time, H 3 BO 3 , continue stirring in a water bath to obtain solution A;

[0010] (3) The Ca(NO 3 ) 2 ·4H 2 O、(CH 3 COO 2 Zn·2H 2 O. KNO 3 、NaNO 3 、Al(NO 3 ) 3 9H 2 O, add the same volume of distilled water as in step (2) and keep in a water bath and fully dissolve to obtain solution B;

[0011] (4) Weighing BN nanosheets and CTAB according to the ratio, adding water, mixing and dispersing by ultrasonic stirring to obtain a completely dispersed BN dispersion;

[0012] (5) slowly adding the A solution obtained in step (2) dropwise into the B solution, and then adding the BN dispersion prepared in step (4) and continuing to stir until a wet gel is obtained; after the gel is formed, drying it in an oven to obtain a dry gel;

[0013] (6) Grinding and preheating the dry gel obtained in step (5) at a pre-burning temperature of 600-700°C for 2-4 hours at a heating rate of 3-5°C / min to obtain a pre-burned powder;

[0014] (7) adding a polyvinyl alcohol binder to the pre-burned powder obtained in step (6), mixing and granulating the mixture in an agate mortar to obtain a pre-prepared powder with good fluidity;

[0015] (8) Pressing the prefabricated powder obtained in step (7) by dry pressing, and keeping the formed ceramic green body at 500-600° C. for 4-8 hours for debinding;

[0016] (9) The ceramic green body after debinding in step (8) is subjected to high temperature sintering to obtain a high thermal conductivity low temperature co-fired ceramic, with a heating rate of 3-5°C / min, a holding time of 4-6h, and a sintering temperature of 950-975°C.

[0017] Preferably, the water-silicon molar ratio required in the mixing process described in steps (2) and (3) is (8-12):1, and the alcohol-silicon volume ratio is (2-7):1; the solution pH is 1-3, the stirring time is 0.5-2h, and the water bath temperature is 60-80°C.

[0018] Preferably, the composite dosage of BN nanosheets described in step (4) is 1-5wt% of the total mass of calcium borosilicate glass ceramics, the ultrasonic dispersion time is 2-5h, and the pH is 9-10.

[0019] Preferably, in step (7), the mass ratio of polyvinyl alcohol binder to prefabricated powder is 1:(13-17).

[0020] Preferably, the pressing pressure in step (8) is 100-200 MPa, and the holding time is 1-2 min.

[0021] Beneficial Effects

[0022] The method for preparing high thermal conductivity low temperature co-fired ceramics proposed in the present invention increases the thermal conductivity of low temperature co-fired ceramic materials to more than 93% on the original basis. Without adding new materials to improve the interface thermal resistance, the thermal conductivity is 1.41~1.84W / m·k; it proves the effectiveness of BN nanosheets as a high thermal conductivity additive in improving the thermal conductivity of materials. It is expected to improve the current situation of poor heat dissipation performance of electronic components such as integrated circuit substrates, radio frequency components and couplers. In addition, while broadening the design range of LTCC material composition, it reduces the sintering temperature of material preparation, which also has a good promoting effect on energy conservation, emission reduction and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The features, advantages and technical effects of exemplary embodiments of the present application will be described below with reference to the accompanying drawings.

[0024] Figure 1 1 is the XRD diagram of the high thermal conductivity low temperature co-fired ceramics of Examples 1 to 3.

[0025] Figure 2 This is the surface SEM image of the high thermal conductivity low temperature co-fired ceramic of Example 1.

[0026] Figure 3 This is the surface SEM image of the high thermal conductivity low temperature co-fired ceramic of Example 2.

[0027] Figure 4 This is the surface SEM image of the high thermal conductivity low temperature co-fired ceramic of Example 3. DETAILED DESCRIPTION

[0028] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0029] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the endpoints of the range is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0030] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number, the "multiple" in "one or more" means two or more, and the "multiple" in "one or more" means two or more.

[0031] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided through a series of examples, and these embodiments can be used in various combinations. In each embodiment, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0032] Example

[0033] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0034] Example 1

[0035] The steps for preparing the high thermal conductivity low temperature co-fired ceramic material described in this embodiment are as follows:

[0036] (1) Ca(NO 3 ) 2 ·4H 2 O, H 3 BO 3 , C 8 H 20 O 4 Si, (CH 3 COO 2 Zn·2H 20 、NaNO 3 、KNO 3 、Al(NO 3 ) 3 9H 2 O is the precursor, and the oxide ratio of glass ceramic is 39% CaO, 20% B 2 O 3 、38%SiO 2 、2% ZnO、0.3% Na 2 O, 0.2%K 2 O, 0.5%Al 2 O 3 Calculate the mass of the precursor and weigh it;

[0037] (2) Press C 8 H 20 O 4 Si:C 2 H 5 The volume ratio of OH is 1:2. Take the corresponding volume of C 2 H 5 OH was used as solvent, distilled water was added at a water-silicon molar ratio of 8:1, and HNO 3 As catalyst, adjust pH to 1, stir in a water bath at 60℃ for 0.5h, then add H 3 BO 3 , continue stirring in a water bath to obtain solution A;

[0038] (3) The Ca(NO 3 ) 2 ·4H 2 O、(CH 3 COO 2 Zn·2H 2 O. KNO 3 、NaNO 3 、Al(NO 3 ) 3 9H 2 O, add the same volume of distilled water as in step (2) and maintain in a water bath at 60 ° C and fully dissolve to obtain a solution B;

[0039] (4) weighing 1wt% of BN nanosheets and 1wt% of CTAB as a dispersant in calcium borosilicate glass ceramics, adding distilled water, mixing with ultrasonic stirring for 0.5h, and adjusting the pH to 9;

[0040] (5) slowly adding the solution A obtained in step (2) dropwise to the solution B, and then adding the BN dispersion prepared in step (4) and continuing to stir until a wet gel is obtained; after the gel is formed, drying it in an oven at 80°C for 12 hours to obtain a dry gel;

[0041] (6) grinding and preheating the dry gel obtained in step (5) at a pre-calcination temperature of 600 ° C for 2 h at a heating rate of 3 ° C / min to obtain a pre-calcined powder;

[0042] (7) adding a polyvinyl alcohol binder to the pre-burned powder obtained in step (6), polyvinyl alcohol binder: pre-burned powder = 1:13, mixing and granulating in an agate mortar to obtain a prefabricated powder with good fluidity;

[0043] (8) dry pressing the preformed powder obtained in step (7) was pressed at a pressure of 100 MPa for 1 min, and the formed ceramic green body was kept at 500 ° C for 8 h for debinding;

[0044] (9) The ceramic green body after debinding in step (8) is sintered at 950° C. The heating rate is 3° C. / min, and the holding time is 4 to 6 hours to obtain a high thermal conductivity low-temperature co-fired ceramic.

[0045] The XRD spectrum of the ceramic is shown in the attached Figure 1 As shown, the main crystal phase is CaSiO 3 and CaB 2 O 4 and CaAl 2 Si 2 O 8 , no impurities are generated. The surface morphology of the ceramic is shown in the attached SEM. Figure 2As shown in the figure, it can be seen that the ceramic has a high density, few pores, and a bulk density of 1.7g / cm 3 According to the thermal conductivity analysis, the thermal conductivity is 1.84W / m·k and the endothermic peak is 800℃.

[0046] Example 2

[0047] The steps for preparing the high thermal conductivity low temperature co-fired ceramic material described in this embodiment are as follows:

[0048] (1) Ca(NO 3 ) 2 ·4H 2 O, H 3 BO 3 , C 8 H 20 O 4 Si, (CH 3 COO 2 Zn·2H 20 、NaNO 3 、KNO 3 、Al(NO 3 ) 3 9H 2 O is the precursor, and the oxide ratio of glass ceramic is 35% CaO, 22% B 2 O 3 、40%SiO 2 、1% ZnO、0.6% Na 2 O, 0.6%K 2 O, 0.8%Al 2 O 3 Calculate the mass of the precursor and weigh it;

[0049] (2) Press C 8 H 20 O 4 Si:C 2 H 5 The volume ratio of OH is 1:4. Take the corresponding volume of C 2 H 5 OH was used as solvent, distilled water was added at a water-silicon molar ratio of 10:1, and HNO 3 As catalyst, adjust pH to 2, stir in a water bath at 70℃ for 1.5h, then add H 3 BO 3 , continue stirring in a water bath to obtain solution A;

[0050] (3) The Ca(NO 3 ) 2 ·4H 2 O、(CH 3 COO 2 Zn·2H2 O. KNO 3 、NaNO 3 、Al(NO 3 ) 3 9H 2 O, add the same volume of distilled water as in step (2) and maintain in a water bath at 70 ° C and fully dissolve to obtain a solution B;

[0051] (4) 3wt% of BN nanosheets and 1wt% of CTAB were weighed in calcium borosilicate glass ceramics, wherein CTAB was used as a dispersant, and distilled water was added and mixed with ultrasonic stirring for 1h to disperse, and the pH was adjusted to 9;

[0052] (5) slowly adding the solution A obtained in step (2) dropwise to the solution B, and then adding the BN dispersion prepared in step (4) and continuing to stir until a wet gel is obtained; after the gel is formed, drying it in an oven at 80°C for 12 hours to obtain a dry gel;

[0053] (6) grinding and preheating the dry gel obtained in step (5) at a pre-calcination temperature of 650 ° C for 3 h at a heating rate of 4 ° C / min to obtain a pre-calcined powder;

[0054] (7) Adding a polyvinyl alcohol binder to the pre-burned powder obtained in step (6), the polyvinyl alcohol binder: pre-burned powder = 1:15, mixing and granulating in an agate mortar to obtain a prefabricated powder with good fluidity;

[0055] (8) dry pressing the preformed powder obtained in step (7) was pressed at a pressure of 150 MPa for 1 min, and the formed ceramic green body was kept at 550 ° C for 6 h for debinding;

[0056] (9) The ceramic green body after debinding in step (8) is sintered at 960° C. with a heating rate of 4° C. / min and a holding time of 5 h to obtain a high thermal conductivity low-temperature co-fired ceramic.

[0057] XRD spectrum of ceramics Figure 1 Similarly, the main crystalline phase is CaSiO 3 and CaB 2 O 4 and CaAl 2 Si 2 O 8 , no impurities are generated. The surface morphology of the ceramic is shown in the attached SEM. Figure 3 As shown in the figure, it can be seen that the ceramic has a high density, few pores, and a bulk density of 1.9g / cm 3 According to the thermal conductivity analysis, the thermal conductivity is 1.65W / m·k and the endothermic peak is 810℃.

[0058] Example 3

[0059] The steps for preparing the high thermal conductivity low temperature co-fired ceramic material described in this embodiment are as follows:

[0060] (1) Ca(NO 3 ) 2 ·4H 2 O, H 3 BO 3 , C 8 H 20 O 4 Si, (CH 3 COO 2 Zn·2H 20 、NaNO 3 、KNO 3 、Al(NO 3 ) 3 9H 2 O is the precursor, and the ratio of oxides in glass ceramic composition is 46% CaO, 16% B 2 O 3 、35%SiO 2 、1% ZnO、0.6% Na 2 O, 0.4%K 2 O, 1%Al 2 O 3 Calculate the mass of the precursor and weigh it;

[0061] (2) Press C 8 H 20 O 4 Si:C 2 H 5 The volume ratio of OH is 1:7. Take the corresponding volume of C 2 H 5 OH was used as solvent, distilled water was added at a water-silicon molar ratio of 12:1, and HNO 3 As catalyst, adjust pH to 3, stir in a water bath at 80℃ for 0.5h, then add H 3 BO 3 , continue stirring in a water bath to obtain solution A;

[0062] (3) The Ca(NO 3 ) 2 ·4H 2 O、(CH 3 COO 2 Zn·2H 2 O. KNO 3 、NaNO 3 、Al(NO 3 ) 3 9H 2O, add the same volume of distilled water as in step (2) and maintain in a water bath at 80 ° C and fully dissolve to obtain a solution B;

[0063] (4) 5wt% of BN nanosheets and 1wt% of CTAB were weighed in calcium borosilicate glass ceramics, wherein CTAB was used as a dispersant, and distilled water was added and mixed with ultrasonic stirring for 2h, and the pH was adjusted to 10;

[0064] (5) slowly adding the solution A obtained in step (2) dropwise to the solution B, and then adding the BN dispersion prepared in step (4) and continuing to stir until a wet gel is obtained; after the gel is formed, drying it in an oven at 80°C for 12 hours to obtain a dry gel;

[0065] (6) grinding and preheating the dry gel obtained in step (5) at a pre-burning temperature of 700 ° C for 4 h at a heating rate of 5 ° C / min to obtain a pre-burned powder;

[0066] (7) Adding a polyvinyl alcohol binder to the pre-burned powder obtained in step (6), the polyvinyl alcohol binder: pre-burned powder = 1:17, mixing and granulating in an agate mortar to obtain a prefabricated powder with good fluidity;

[0067] (8) dry pressing the preformed powder obtained in step (7) was pressed at a pressure of 200 MPa for 2 min, and the formed ceramic green body was kept at 600 ° C for 4 h for debinding;

[0068] (9) The ceramic green body after debinding in step (8) is sintered at 975° C. with a heating rate of 5° C. / min and a holding time of 6 h to obtain a high thermal conductivity low temperature co-fired ceramic.

[0069] The XRD spectrum of the ceramic is shown in the attached Figure 1 Similarly, the main crystalline phase is CaSiO 3 and CaB 2 O 4 and CaAl 2 Si 2 O 8 , no impurities are generated. The surface morphology of the ceramic is shown in the attached SEM. Figure 4 As shown in the figure, it can be seen that the ceramic has a high density, few pores, and a bulk density of 1.8g / cm 3 According to the thermal conductivity analysis, the thermal conductivity is 1.41W / m·k and the endothermic peak is 810℃.

[0070] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A high thermal conductivity low temperature co-fired ceramic, It is characterized in that BN nanosheets are compounded in a calcium borosilicate glass ceramic matrix, wherein the calcium borosilicate glass ceramic is composed of CaO, B 2 O 3 、SiO 2 、ZnO、Na 2 O.K 2 O、Al 2 O 3 According to the molar percentage composition of (35-50%): (15-20%): (35-40%): (1-5%): (0-1%): (0-1%): (0.5-1%), the sum of the molar percentages of each component is 100%, and the composite dosage of the BN nanosheet is 1-5wt% of the total mass of the calcium borosilicate glass ceramic; the preparation method of the high thermal conductivity low temperature co-fired ceramic material is a sol-gel method, comprising the following steps: (1) Ca(NO 3 ) 2 ·4H 2 O, H 3 BO 3 , C 8 H 20 O 4 Si, (CH 3 COO 2 Zn·2H 2 O.NaNO 3 、KNO 3 、Al(NO 3 ) 3 9H 2 O is the precursor, and the mass of the precursor is calculated according to the oxide ratio of the glass ceramic composition and weighed for later use; (2) Add the C weighed in step (1) 8 H 20 O 4 Si was fully mixed with ethanol and water, and stirred in a water bath to obtain a mixed solution; after a certain period of time, H 3 BO 3 , continue stirring in a water bath to obtain solution A; (3) The Ca(NO 3 ) 2 ·4H 2 O、(CH 3 COO 2 Zn·2H 2 O. KNO 3 、NaNO 3 、Al(NO 3 ) 3 9H 2 O, add the same volume of distilled water as in step (2) and keep in a water bath and fully dissolve to obtain solution B; (4) Weighing BN nanosheets and CTAB according to the ratio, adding water, mixing and dispersing by ultrasonic stirring to obtain a completely dispersed BN dispersion; (5) slowly adding the solution A obtained in step (2) dropwise to the solution B obtained in step (3), and then adding the BN dispersion prepared in step (4) and continuing to stir until a wet gel is obtained; after the gel is formed, drying it in an oven at 80°C for 12 hours to obtain a dry gel; (6) Grinding and preheating the dry gel obtained in step (5) at a pre-burning temperature of 600-700°C for 2-4 hours at a heating rate of 3-5°C / min to obtain a pre-burned powder; (7) adding polyvinyl alcohol to the pre-burned powder obtained in step (6), mixing and granulating the mixture in an agate mortar to obtain a pre-prepared powder with good fluidity; (8) Pressing the prefabricated powder obtained in step (7) by dry pressing, and keeping the formed ceramic green body at 500-600° C. for 4-8 hours for debinding; (9) The ceramic green body after debinding in step (8) is subjected to high temperature sintering to obtain a high thermal conductivity low temperature co-fired ceramic, with a heating rate of 3-5°C / min, a holding time of 4-6h, and a sintering temperature of 950-975°C.

2. The method for preparing the high thermal conductivity low temperature co-fired ceramic according to claim 1, It is characterized in that The water-silicon molar ratio required in the mixing process described in steps (2) and (3) is (8-12):1, and the alcohol-silicon volume ratio is (2-7):1; the solution pH is 1-3, the stirring time is 0.5-2h, and the water bath temperature is 60-80°C.

3. The method for preparing the high thermal conductivity low temperature co-fired ceramic according to claim 1, It is characterized in that The BN nanosheet composite dosage described in step (4) is 1-5wt% of the total mass of the calcium borosilicate glass ceramic, the ultrasonic dispersion time is 2-4h, and the pH is 9-10.

4. The method for preparing the high thermal conductivity low temperature co-fired ceramic according to claim 1, It is characterized in that In step (7), the mass ratio of polyvinyl alcohol binder: prefabricated powder is 1:(13-17).

5. The method for preparing the high thermal conductivity low temperature co-fired ceramic according to claim 1, It is characterized in that The pressing pressure in step (8) is 100-200 MPa, and the holding time is 1-2 min.